2005
DOI: 10.1124/mol.105.011304
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lasting Impairment of Associative Learning Is Correlated with a Dysfunction of N-Methyl-d-aspartate-Extracellular Signaling-Regulated Kinase Signaling in Mice after Withdrawal from Repeated Administration of Phencyclidine

Abstract: In humans, the administration of phencyclidine causes schizophrenic-like symptoms that persist for several weeks after withdrawal from phencyclidine use. We demonstrated here that mice pretreated with phencyclidine (10 mg/kg/day s.c. for 14 days) showed an enduring impairment of associative in a Pavlovian fear conditioning 8 days after cessation of phencyclidine treatment. Extracellular signaling-regulated kinase (ERK) was transiently activated in the amygdalae and hippocampi of saline-treated mice after condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…Thus, NMDA receptor antagonists, such as phencyclidine, MK-801, and ketamine, induce psychotic states in normal human volunteers and exacerbate symptoms in patients with schizophrenia (Javitt and Zukin, 1991;Olney et al, 1999). Based on the results of the present study and the previously reported finding that the phencyclidine-treated animal, a useful model of schizophrenia, induces a long-lasting impairment of associative learning accompanied by a decrease in learning-associated NMDA-ERK signaling (Enomoto et al, 2005), nobiletin might improve the cognitive impairment associated with schizophrenia through activation of ERK signaling. Furthermore, it is necessary to investigate the beneficial effects of nobiletin on schizophrenia-like positive and negative symptoms in animal models of schizophrenia in the future study.…”
Section: Downloaded Frommentioning
confidence: 87%
See 1 more Smart Citation
“…Thus, NMDA receptor antagonists, such as phencyclidine, MK-801, and ketamine, induce psychotic states in normal human volunteers and exacerbate symptoms in patients with schizophrenia (Javitt and Zukin, 1991;Olney et al, 1999). Based on the results of the present study and the previously reported finding that the phencyclidine-treated animal, a useful model of schizophrenia, induces a long-lasting impairment of associative learning accompanied by a decrease in learning-associated NMDA-ERK signaling (Enomoto et al, 2005), nobiletin might improve the cognitive impairment associated with schizophrenia through activation of ERK signaling. Furthermore, it is necessary to investigate the beneficial effects of nobiletin on schizophrenia-like positive and negative symptoms in animal models of schizophrenia in the future study.…”
Section: Downloaded Frommentioning
confidence: 87%
“…Reversely, in vivo blockade of NMDA receptors or inhibition of ERK signaling results in impairment of associative learning (Kim et al, 1991;Atkins et al, 1998). Furthermore, long-lasting impairment of associative learning after repeated administration of phencyclidine, a noncompetitive NMDA receptor antagonist, is correlated with a dysfunction of ERK signaling (Enomoto et al, 2005). Accordingly, it is plausible that control of ERK signaling is a potential target for treatment of neurological disorders exhibiting cognitive dysfunction.…”
mentioning
confidence: 99%
“…The cued and contextual fear-conditioning tasks were carried out on the days 9-10 after Ab 25À35 infusion according to a previous report (Enomoto et al, 2005) with a minor modification. For measuring basal levels of freezing response (preconditioning phase), on the day 9, mice were individually placed in a neutral cage (23 Â 23 Â 12 cm) for 1 min and then in the conditioning cage (25 Â 31 Â 11 cm) for 2 min.…”
Section: Cued and Contextual Fear-conditioning Testsmentioning
confidence: 99%
“…Accordingly, rodents and nonhuman primates treated with non-competitive NMDAR antagonists display behavioral features consistent with many symptoms of schizophrenia . Repeated dosing with these drugs may provide greater validity than acute administration, as such regimens induce neurochemical changes similar to those seen in schizophrenic patients (Cochran et al, 2003;Enomoto et al, 2005;Reynolds et al, 2004), as well as lasting cognitive deficits that can be observed when animals are tested in a drug-free state (Jentsch and Roth, 1999).…”
Section: Introductionmentioning
confidence: 99%